Genomic Imprinting Mechanisms in Mammals - Ideraabdullah, Folami Y. (2008)
Genomic imprinting is a form of epigenetic gene regulation that results in expression from a single allele in a parent-of-origin-dependent manner. This form of monoallelic expression affects a small but growing number of genes and is essential to normal mammalian development. Despite extensive studies and some major breakthroughs regarding this intriguing phenomenon, we have not yet fully characterized the underlying molecular mechanisms of genomic imprinting. This is in part due to the complexity of the system in that the epigenetic markings required for proper imprinting must be established in the germline, maintained throughout development, and then erased before being re-established in the next generation’s germline. Furthermore, imprinted gene expression is often tissue or stage-specific. It has also become clear that while imprinted loci across the genome seem to rely consistently on epigenetic markings of DNA methylation and/or histone modifications to discern parental alleles, the regulatory activities underlying these markings vary among loci. Here, we discuss different modes of imprinting regulation in mammals and how perturbations of these systems result in human disease. We focus mostly on the mechanism of genomic imprinting mediated by insulators as is present at the H19/Igf2 locus, and by non-coding RNA present at the Igf2r and Kcnq1 loci. In addition to imprinting mechanisms at autosomal loci, what is known about imprinted X-chromosome inactivation and how it compares to autosomal imprinting is also discussed. Overall, this review summarizes the many years of imprinting research, while pointing out exciting new discoveries that further elucidate the mechanism of genomic imprinting, and speculating on areas that require further investigation.